2021
DOI: 10.1002/chem.202100168
|View full text |Cite
|
Sign up to set email alerts
|

Proton‐Transfer Dynamics of Photoacidic Merocyanines in Aqueous Solution

Abstract: Photoacids attract increasing scientific attention, as they are valuable tools to spatiotemporally control protonrelease reactions and pH values of solutions. We present the first time-resolved spectroscopic study of the excited state and proton-release dynamics of prominent merocyanine representatives. Femtosecond transient absorption measurements of a pyridine merocyanine with two distinct protonation sites revealed dissimilar proton-release mechanisms: one site acts as a photoacid generator as its pK a valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 84 publications
(135 reference statements)
2
26
0
Order By: Relevance
“…The p K a h ν value determined under irradiation can be viewed as the p K a value of the cis -MCH form because the equilibrium between cis- MC and SP is shifted entirely to SP when irradiated. The cis -MC form is short-lived and can only be detected by transient absorption spectroscopy, , whereas cis -MCH is stable at low pH values (determined by p K a h ν ). , In earlier studies, the cis -MCH was assigned as the protonated spiropyran (SPH). ,,, More recent work has shown that the assignment as cis -MCH is most appropriate . From a practical perspective, cis -MCH behaves mechanistically as SPH due to an apparent barrierless transition from SP to cis -MCH at low pH …”
Section: Resultsmentioning
confidence: 99%
“…The p K a h ν value determined under irradiation can be viewed as the p K a value of the cis -MCH form because the equilibrium between cis- MC and SP is shifted entirely to SP when irradiated. The cis -MC form is short-lived and can only be detected by transient absorption spectroscopy, , whereas cis -MCH is stable at low pH values (determined by p K a h ν ). , In earlier studies, the cis -MCH was assigned as the protonated spiropyran (SPH). ,,, More recent work has shown that the assignment as cis -MCH is most appropriate . From a practical perspective, cis -MCH behaves mechanistically as SPH due to an apparent barrierless transition from SP to cis -MCH at low pH …”
Section: Resultsmentioning
confidence: 99%
“…The absence of a hydrogen-atom can also prevent possible non-radiative decay upon hydrogen-bonding with protic solvents [34][35][36][37]39] and eliminates a potentially photoacidic site. [40,41] The synthesis of compounds 7 a-d started from commercially available m-aminophenol 2 (see Figure 3a). In the first step, the hydroxy group of 2 was protected with tertbutyldimethylsilyl (TBDMS) in a quantitative yield.…”
Section: Resultsmentioning
confidence: 99%
“…This exhibits an electron donating character compared to the proton in 7 a and 7 c and should thus enhance the charge transfer character formation originating from the nitrogen that is necessary for uncaging. The absence of a hydrogen‐atom can also prevent possible non‐radiative decay upon hydrogen‐bonding with protic solvents [34–37,39] and eliminates a potentially photoacidic site [40,41] …”
Section: Resultsmentioning
confidence: 99%
“…Transient absorption spectroscopy was also used by Wachtveitl's group to study the photoreaction of a pyridinyl merocyanine photoacid. 14 Physicochemical properties, e.g. acidity, reverse reaction rate etc.…”
Section: Structure and Mechanism Of Mpahsmentioning
confidence: 99%